Psalm 9.22-26 in a 4th-Century Papyrus from the Western Desert in Egypt - Worp, Klaas Anthony (Vetus Testamentum, 2016)
First edition of a Psalm fragment on a Greek papyrus coming from a settlement in the Western desert of Egypt. Discussion of its religious background (Jewish, Manichaean,or Christian?) and of its possible use, as an amulet? Attention is paid to a textual variant.